On stratifications for planar tensegrities with a small number of vertices - Karpenkov, Oleg (Ars mathematica contemporanea, 2013)
In this paper we discuss several results about the structure of the configuration space of two-dimensional tensegrities with a small number of points. We briefly describe the technique of surgeries that is used to find geometric conditions for tensegrities. Further we introduce a new surgery for three-dimensional tensegrities. Within this paper we formulate additional openproblems related to the stratified space of tensegrities.
Keywords: equilibrium; surgeries; tensegrities